(untitled) (Web of Teachers: Inderscience Research, 2025)
This article presents several methods of effective teaching of English, as well as popular methods of teaching and learning English, as well as Internet resources. During the writing of the article, the principles of theoretical-deductive inference, analysis and synthesis, and logic were used.